Synthesis, Characterization, Crystal Structure and Antibacterial Activities of Transition Metal(II) Complexes of Schiff Base - Yu, Yu-Ye; Zhao, Guo-Liang; Liu, Jian-Feng (Asian Journal of Chemistry, 2010)
Five complexes of the general composition [ML2(NO3)2] (1-5) [M = Mn(II),Co(II), Ni(II), Cu(II), Cd(II)] were synthesized from the reaction of a Schiff base ligand 2-[(4-methylphenylimino)- methyl]-6-methoxy-phenol (C15H15NO2, L) and M(NO3)2·nH2O, where the Schiff base was obtained by condensation of o-vanillin (2-hydroxy-3-methoxybenzaldehyde) with p-toluidine. They were characterized by elemental analysis, molar conductance, FT-IR, UV-vis spectra and thermal analysis. The structure of complex 1 was deterimend by single-crystal X-ray diffraction technique. It's crystal structure is of triclinic, space group P-1 with a = 0.93135(4), b = 1.04613(4), c = 1.77348(7) nm, a = 73.868(2), b = 85.681(2), g = 64.902(2)º, V = 1.50137(10) nm3, Z = 2, Mr = 661.52, F(000) = 686, Dc = 1.463 g cm-3, μ (M0Ka) = 0.504 mm-1. Schiff base and it's metal complexes have been tested in vitro to evaluate their antibacterial activity against bacteria, viz., Escherichia coli, Staphylococcus aureus and Bacillus subtilis. It has been found that all the metal complexes have higher activity than the corresponding free Schiff base ligand against these bacteria and the Cd(II) complex has the highest activity.